2022
DOI: 10.1159/000522436
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Patients with Hematologic Malignancies: Outcomes and Options for Treatments

Abstract: Patients with hematologic malignancies are particularly vulnerable to infections due to underlying humoral and cellular immune dysfunction, cytotoxic chemotherapy regimens, advanced age, and the presence of comorbid conditions. Infection from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of the COVID-19 pandemic, has become a leading cause of death globally and has disproportionally affected this high-risk population. Here, we review the cumulative evidence demonstrating wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 95 publications
3
9
0
5
Order By: Relevance
“…A SARS‐CoV‐2 infection required hospitalisation of our patients during their therapy with MOL if the ECOG performance status was poor (ECOG ≤ 2, P = .007) and haemoglobin levels were equal to or lower than 10 g/dL ( P = .0385). The impact of advanced age was on the verge of statistical, even though it is consistently associated with worse COVID‐19 outcomes and conducive to raising the baseline risk of a severe COVID‐19 infection in patients with haematological malignancies 15,19 . Interestingly, in multivariate analyses, our study showed significant differences in the need of hospitalisation when we compared younger (<60 years old) vaccinated patients to older unvaccinated ones ( P = .029; 4.0 [1.33‐11.03]), which corroborates the results of other observational studies 15,19 …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A SARS‐CoV‐2 infection required hospitalisation of our patients during their therapy with MOL if the ECOG performance status was poor (ECOG ≤ 2, P = .007) and haemoglobin levels were equal to or lower than 10 g/dL ( P = .0385). The impact of advanced age was on the verge of statistical, even though it is consistently associated with worse COVID‐19 outcomes and conducive to raising the baseline risk of a severe COVID‐19 infection in patients with haematological malignancies 15,19 . Interestingly, in multivariate analyses, our study showed significant differences in the need of hospitalisation when we compared younger (<60 years old) vaccinated patients to older unvaccinated ones ( P = .029; 4.0 [1.33‐11.03]), which corroborates the results of other observational studies 15,19 …”
Section: Resultssupporting
confidence: 88%
“…Surprisingly, our study showed no correspondence between the need for hospitalisation of vaccinated and nonvaccinated patients (Table 2). Therefore, an even greater difference is visible in the use of MOL in comparison to haematology patients if we analyse the mortality rates before the prevaccination period which then stood at approximately 31% 15 …”
Section: Resultsmentioning
confidence: 99%
“…Active COVID-19 infection gives most oncologists a pause when it comes to starting treatment for infected patients' malignant hematologic disorders. Prior studies have indicated worse COVID-19 outcomes in patients with acute myeloid leukemia (AML) receiving cancer treatment [ 1 , 2 ]. Weighing the risks and benefits of withholding treatment until infection clearance in an already immunocompromised host is done on a case-by-case basis with careful consideration of the best outcome for patients.…”
Section: Introductionmentioning
confidence: 99%
“…The dedication of efforts to a better understanding of why patients with hematologic malignancies are particularly susceptible to worse COVID-19 outcomes and disproportionately affected by the deaths that such outcomes cause has been urged. 14 And at this juncture, we ought to ask the following important question that we have been given the capacity to begin answering in this paper: What predicts those who will suffer from the severe outcomes of the concomitant appearance of the infectious disease and the diseases in its immunological spectrum?" The answer that emerges from the reality we have illustrated, which must correspond with experience before we accept it, is this: "The presence, even before pathological mechanisms respond to the influence of the pathogen, of the causes of such diseases which, through the co-appearance of their manifestations with those of the disease the pathogen causes, expose the infected to such severe outcomes.…”
mentioning
confidence: 99%